Design of an MPPT Monitoring System for a Solar Power Plant Based on the Internet of Things Using ESP32 and Thing Speak - Pujianto Pujianto; M Zaky Zaim Muhtadi; Miranda Odilia Lambiombir (International Journal of Science and Environment (IJSE), 2026)
This study designed and implemented an Internet of Things (IoT)-based telemetry system to monitor electrical parameters in a solar power plant (SPP) installation equipped with a Maximum Power Point Tracking (MPPT) controller. The system was developed using an ESP32 microcontroller connected to an EPever MPPT controller via RS485-based Modbus RTU communication, which then transmits data in real-time over a WiFi network to the ThingSpeak cloud platform for storage, visualization, and remote monitoring. The research method used was descriptive-experimental, covering hardware and software design, communication testing, and operational data acquisition. The observed parameters included input voltage, input current, output voltage, output current, discharge voltage, and discharge current. Test results over the time range of 10:10–17:00—comprising seven sample points with non-uniform intervals—showed a maximum input voltage of 18.35 V with a current of 0.66 A at 13:00, reflecting optimal irradiation conditions, a maximum output voltage of 12.27 V, and relatively stable discharge parameters within a voltage range of 12.64–14.45 V and a current range of 0.05–0.19 A, serving as an indicator of the MPPT controller’s power regulation effectiveness. Analysis of the ThingSpeak graph confirmed that the input voltage pattern followed the daily irradiance curve, the dynamic response of the output voltage to irradiance fluctuations, and the identification of transient anomalies requiring further confirmation with an irradiance sensor. These findings indicate that the ESP32- and ThingSpeak-based telemetry system is suitable for use as an effective and economical PV system monitoring solution, with recommendations for further research including continuous data acquisition at fixed intervals, the addition of a pyranometer, and comparative validation with reference measurement instruments.